Analisis Konten Dakwah Dalam Aplikasi Tik Tok Di Kalangan Remaja - Shafa Tasya Kamilah; Putri Adiniyah Shoheh; Mufti Khairul Zain; Meity Suryandari (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Da'wah for Muslims is a must to make Islamic society stronger. Da'wah plays an important role in regulating a harmonious, peaceful society and of course in accordance with Islamic teachings. Messages, role and facilities of da'wah are the main elements in the process of da'wah itself. Da'wah messages are all material sourced from the Al-Qur'an and Al-Hadith which are the instructions and sources of the main teachings of Islam. In the current era, all Muslims cannot be separated from social media. People are expected to be able to follow the development of this era so as not to be eliminated by the times. As young people who are expected to become leaders in the future, we must be able to take advantage of digital progress to always broadcast the teachings of Islam. One of the uses of digital applications to carry out da'wah is the Tik Tok application. Even though there are many positive impacts on preaching, we as a generation of wise Muslims must be able to minimize the use of Tik Tok so that it does not have a negative impact. If Muslims use the Tik Tok application for da'wah media, it will make Muslims stronger.